Revised estimates of temperature changes under net zero CO2 emissions - Alex Borowiak; Andrew D. King; Josephine R. Brown; Tilo Ziehn (npj Climate and Atmospheric Science)
Abstract It is critical that climate changes beyond net zero are well understood to inform policymaking. Here we present a new estimate of post-abrupt net zero CO2 temperature changes using a method that filters for variability on multiple timescales. Our findings indicate that 50 years after abrupt emission cessation, the multi-model median temperature change is −0.19 °C, with a range spanning from −0.44 °C to 0.04 °C, which is cooler than previous estimates.